The ABCs of Teaching Cross-culturally: University Educators’ Experiences - Dwyer, Sonya Corbin (International Dialogues on Education Journal, 2014)
Not all students have the opportunity to study abroad nor to benefit from having international students in their classes, but they can benefit from having an educator who has taught cross-culturally in an international setting. As Schlein and Garii (2011) explain, educators can use international experiences to become “culturally enhanced” and bring these enhancements back to their classrooms—including (potential) shifts in personal and professional identities. This paper describes the benefits, challenges and advice that 11 university educators offer based on their personal experiences. Given the reported lack of orientation activities, these ABCs may be important in helping to prepare educators considering international projects (as the old idiom goes “forewarned is forearmed”). Further, it can help universities design support services for educators going abroad and for visiting educators to foster a positive experience for the educators and students.